On the accuracy of adults' auditory perception of normophonic and dysphonic children's personality. (3rd July 2015) - Verduyckt, Ingrid; Remacle, Marc; Morsomme, Dominique
Abstract : We investigated the accuracy of auditory inferences of personality of Belgian children with vocal fold nodules (VFN). External judges ( n = 57) were asked to infer the personality of normophonic (NP) children and children with VFN ( n = 10) on the basis of vowels and sentences. The auditory inferred profiles were compared to the actual personality of NP and VFN children. Positive and partly accurate inferences of VFN children's personality were made on the basis of connected speech, while sustained vowels yielded negative and inaccurate inferences of personality traits of children with VFN. Dysphonic voice quality, as defined by the overall severity of vocal abnormality, conveyed inaccurate and low degrees of extraversion. This effect was counterbalanced in connected speech by faster speaking rate that accurately conveyed higher degrees of extraversion, a characteristic trait of VFN children's actual personality.